Sistem Informasi Geografis Analisis dan Pemantauan Gempa (SIGAP) - Ari Purno Wahyu Wibowo; Muhammad Arief Fahrizal (Journal of Information Technology, 2022)
Abstract- The existence of volcanoes that cover almost the entire archipelago in Indonesia has increased the vulnerability factor of Indonesia's territory. In addition, Indonesia's climatic conditions with high rainfall and a relatively long dry season have great potential for the Indonesian population to be subject to floods and even earthquakes that can cause landslides. To overcome this problem, an earthquake and natural disaster information system was created that can be used by the community or the government as a reference for carrying out preventive prevention processes before the disaster becomes more serious or spreads to other locations. This information system can’t only be used by the public to search for geographic information on earthquakes in Indonesia, even throughout the world, this geographic information system can also be implemented in an application platform in the form of a website to increase public awareness of the impact of earthquakes on how to overcome them.